B vitamin supplementation improves cognitive function in the middle aged and elderly with hyperhomocysteinemia. (12th December 2016) - Cheng, Daomei; Kong, Haiyan; Pang, Wei; Yang, Hongpeng; Lu, Hao; Huang, Chengyu; Jiang, Yugang
Abstract : Objective : An intervention study was performed to determine if supplement containing folic acid, vitamin B6, and vitamin B12 could improve cognitive function and lower homocysteine in middle-aged and elderly patients with hyperhomocysteinemia. Methods : One hundred and four participants with hyperhomocysteinemia were recruited in Tianjin, China, aged 55–94 years old. Fifty-seven individuals with hyperhomocysteinemia were included in the intervention group (vitamin B group, which received 800 µg/day of folate, with 10 mg of vitamin B6 and 25 µg of vitamin B12 ) and 47 patients in the placebo group. The endpoint was the improvement in cognitive function as evaluated by Basic Cognitive Aptitude Tests (BCATs). All parameters were measured before and after the treatment period of 14 weeks. Results : The BCAT total score and four sub-tests scores (digit copy, Chinese character rotation, digital working memory, and recognition of meaningless figure) of BCAT at 14 weeks significantly increased only for the vitamin B group. Serum total homocysteine (tHcy) levels significantly decreased in the intervention group, while serum concentrations of folate, vitamin B6, and vitamin B12 significantly increased in the intervention group. Conclusion : The results demonstrated that supplement containing folate, vitamin B6, and vitamin B12 in middle-aged and elderly patients with hyperhomocysteinemia could improve their cognitive function partly and reduce serum tHcy levels.